Analysis of Procedural Negligence by Election Officials and Efforts to Resolve Them in the 2024 General Election - Zulfikar Adjie; Asmun W. Wantu; Yayan Sahi (Jurnal Kewarganegaraan, 2024)
Abstract This study aims to analyze procedural negligence by the election organizing groups and their resolution efforts during the 2024 General Elections. The research method used is qualitative. The study is located in Paguyaman Pantai District. Data sources include primary data obtained from election organizing groups in the research area, and secondary data from archived reports, journals, and books to support the research. Data collection techniques include observation, interviews, and documentation. The research findings identify several instances of procedural negligence, such as errors in distributing ballots to specific polling stations, damage or loss of crucial documents like the C-Notification (containing vote count results), errors in filling out documents like the C-Results, discrepancies between the number of ballots and the Voter List (DPT), and administrative issues related to document delivery. Resolution efforts involve diverse follow-up actions across various polling stations. For example, replacing damaged or incorrectly placed ballots, reconciliation after vote counting, assistance during the counting process, discussions to address absenteeism issues, and re-elections with redistributions of ballots. In conclusion, addressing these instances of procedural negligence requires diverse strategies to ensure the integrity and success of the electoral process. These efforts are crucial to minimize negative impacts on the validity and integrity of democratic processes at each Polling Station. Keywords: Procedural Negligence, Voting Organizing Group, General elections